تجارب عربية في تطبيق الحوكمة الالكترونية مع التركيز على حالة الجزائر Arab Experiences In Application Of E-governance, With A Focus On The Case Of Algeria - بودالي, محمد (جامعة الوادي - University of Eloued, 2021)
عرف العالم تطورا غير مسبوق في مجال تكنولوجيا المعلومات والاتصالات أدى الى بروز شبكة الانترنيت وتطور مختلف الوسائل والتقنيات ما حمل الدول خاصة النامية الى الاسراع في تبني مبادئ الادارة الالكترونية في مؤسساتها وارساء نظام يعتمد على الحوكمة الالكترونية تماشيا مع المتطلبات العالمية وهذا للرفع من كفاءة مؤسساتها بما يضمن منافستها من جهة وتحسين الخدمات العمومية لمواطنيها من جهة أخرى. وسوف نحاول في هذه الورقة البحثية تقييم تجربة الحكومة الجزائرية في مجال الحوكمة الالكترونية وهذا باستعراض أهم الاجراءات الالكترونية التي استحدثتها لتطوير مؤسسات الدولة والادارات المحلية ومقارنتها بتجارب الدول العربية الرائدة في هذا المجال. Abstract: The world has know a huge développent in terms of information and communication technologies which have been characterised by creating the internet network and déveloping the digital techniques and tools. In fact, all the countries of the world have started to implement the principal of digital administration inside their enterprises, and they tried to incarnate a system basing on digital governance. This way has been adopted in order to adapt their environment with the international requirements aiming to enhance the competitiveness of their enterprises and, at the same time, improve the quality of public services. this paper aims to evaluate the experience of the Algerian government concerning the field of corporate governance. Therefore, the paper starts by illustrating the main digital procedures aiming to develop the public enterprises and the local administration. It aims as well to compare them by the experience of some Arabic countries in such domains. Keywords: governance, electronic management, technology, digitization, Arab countries
Keywords: الحوكمة ; الإدارة الإلكترونية ; التكنولوجيا ; الرقمنة ; البلدان العربية